Personal Branding Marketing as An Effort to Strengthen the Entrepreneurial Identity of Mekar Baru Village - Putra, Anshari; Hidayat, Taopik; Pratiwi, Widya Ayu; Hayani, Nurul; Padila, Tasya; Nabilla, N.; Situngkir, Garace Ananda; Manurung, Abdul Jailani; Dewi, Eka Nurshouma; Tobing, Daniel (Golden Ratio of Community Services and Dedication, 2026)
This study aims to analyze the implementation of personal branding marketing as a strategy to strengthen business identity among entrepreneurs in Mekar Baru Village, Batu Bara Regency. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving 15 MSME actors from culinary, handicraft, service, and small trading sectors. The findings reveal that most MSMEs are still managed traditionally with a weak business identity. Only 40% of business owners have implemented basic elements of personal branding, such as logos, consistent brand names, and specially designed packaging. The main obstacles to branding are low digital literacy, limited capital, and a lack of institutional support. Nevertheless, the application of personal branding has shown positive impacts in enhancing customer loyalty, expanding market reach, and strengthening the image of local products. These findings highlight that personal branding marketing is an essential instrument in building the competitiveness of village-based MSMEs, although continuous support from multiple stakeholders is required.